Effects of cyclic-nucleotide derivatives on the growth of human colonic carcinoma xenografts and on cell production in the rat colonic crypt epithelium. - Tutton, P. J. (Nature Publishing Group, 1981)
Previous studies have shown that various amine hormones are able to influence the growth rate of human colorectal carcinomas propagated as xenografts in immune-deprived mice, and it is now well known that the effects of many amine and other hormones are mediated by cyclic nucleotides, acting as second messengers within cells. In the present study the influence of various derivatives of cyclic adenosine monophosphate and cyclic guanosine monophosphate on the growth of two different lines of colorectal cancer growing in immune-deprived mice, and on the cell production rate in the colonic crypt epithelium of the rat, was assessed. Growth of each tumour line, as well as crypt-cell production, was suppressed by treatment wit N6O2' dibutyryl and N6 monobutyryl derivatives of cyclic adenosine monophosphate. Dibutyryl cyclic guanosine monophosphate, on the other hand, was found to promote the growth of Tumour HXK4 and to promote crypt cell production, but to have no significant effect on Tumour HXM2.